Pengaruh Karateristik Personal Auditor Pemerintah Terhadap Tingkat Penerimaan Penyimpangan Perilaku Dalam Audit - Nesya Kartika Rahmawati; Christina Dwi Astuti (JURNAL INFORMASI, PERPAJAKAN, AKUNTANSI, DAN KEUANGAN PUBLIK, 2014)
The compilation of this thesis aimed at knowing the influence between auditor's individual characteristics and their acceptance of dysfunctional audit behavior. This research used the sample totaling 120 respondents from the auditors, who work in government agencies in Jakarta. The available questionnaire was distributed by convenience methods. The analysis method of the data that was used structural equation modeling as a tool of analysis using the LISREL program. Results of the research showed that externality in auditor 's locus of control and turnover intention have significant positive relationships with the level of acceptance of dysfunctional behavior, while the self-rate auditor performance have insignificant negative relationships with the level of acceptance of dysfunctional behavior, and self-esteem in relation to ambition have insignificant positive relationships with the level of acceptance of dysfunctionul behavior.